Zinc-coated Mn-containing advanced high-strength steel and its manufacturing method
A manganese-containing galvanized steel sheet with controlled annealing treatment forms a decarburized ferrite sublayer and internal oxidation zones, addressing manganese oxidation and LME issues, ensuring effective zinc coverage and reduced weld cracks.
Patent Information
- Application Number
- JP2024531074
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-11-24
- Filing Date
- 2022-10-17
- Publication Date
- 2024-12-20
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing galvanized steel sheets face issues with manganese oxidation leading to reduced zinc coverage and adhesion, as well as susceptibility to liquid metal embrittlement (LME) during welding, particularly in high-strength steels with manganese content.
A galvanized steel sheet with controlled manganese content (3.0-6.0%) and specific annealing treatment involving preheating, radiant tube heating, soaking, and cooling under controlled atmospheres to form a decarburized ferrite sublayer and internal oxidation zones, ensuring good zinc coverage and LME resistance.
The solution achieves improved zinc coverage and resistance to LME, with reduced carbon content and controlled oxidation zones enhancing the steel's mechanical properties and weldability, resulting in fewer cracks in spot-welded joints.
Smart Images

Figure 2024546369000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a manganese-containing galvanized high strength steel sheet having good coatability with liquid zinc and good weldability properties. The present invention also relates to a method for obtaining such a steel sheet. [Background technology]
[0002] One of the developments that has been made to improve the mechanical properties is to increase the content of manganese in the steel. The presence of manganese helps to increase the ductility of the steel thanks to the stabilization of the austenite.
[0003] In addition to the mechanical requirements, steel sheets need good coating ability when immersed in a zinc or zinc alloy galvanizing bath. This coating ability depends on the surface, especially on the presence of oxides. Manganese in steel is an element that easily oxidizes, and therefore reacts with oxygen and water vapor in the annealing furnace to form oxides on the steel sheet surface. Manganese oxides reduce the coating ability of the steel sheet in liquid zinc and the subsequent adhesion of the zinc coating.
[0004] Such steels should also exhibit good resistance to liquid metal embrittlement (LME). Zinc or zinc alloy coated steels are very effective at resisting corrosion and are therefore widely used in the automotive industry. However, it has been experienced that arc or resistance welding of certain steels can cause crack initiation due to a phenomenon called liquid metal embrittlement ("LME") or liquid metal assisted cracking ("LMAC"). This phenomenon is characterized by the penetration of liquid zinc along grain boundaries of the underlying steel substrate under applied or internal stresses resulting from restraint, thermal expansion or phase transformation. The addition of elements such as carbon or silicon is known to be detrimental to LME resistance.
[0005] Patent EP3396005 discloses the production of galvanized steel sheet containing 3-8 wt% manganese. It deals with the control of the surface selective oxidation of manganese to eliminate non-uniform alloying. The patent discloses a step B of heating the steel sheet to 550°C-700°C in a direct fired furnace (DFF) using combustion gas with an air ratio of 1.00-1.20, and holding the steel sheet at a temperature of 550°C-700°C for 30 seconds or less, and a step C of holding the steel sheet at 550°C-700°C for 10-300 seconds in a reducing atmosphere with a hydrogen concentration of 1-50% by volume. However, such a heat treatment cannot completely recrystallize the steel sheet and is not favorable for LME resistance.
[0006] Patent EP3020842 discloses the production of galvanized steel sheets containing 2-4 wt.% manganese. It describes oxidation carried out in an oxidation zone at an air-fuel ratio of 0.9-1.4 before the sheet is soaked above Ac3 in a reducing atmosphere with a controlled dew point of -30°C to -60°C. During oxidation, an iron oxide film can be formed on the surface, reducing the formation of a composite oxide film of silicon and manganese, which is detrimental to galvanizability. Decarburization also occurs, forming a desired soft layer and improving bending workability. Furthermore, an inner oxide layer is included in such a soft layer and can be used as a hydrogen trap to improve hydrogen embrittlement.
[0007] However, this patent does not describe the heating step, nor does it disclose the heating rate of the heating step prior to the soaking step. Furthermore, this patent does not address the issue of resistance to liquid metal embrittlement. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] European Patent No. 3396005 [Patent Document 2] European Patent No. 3020842 Summary of the Invention [Problem to be solved by the invention]
[0009] The object of the present invention is to provide a steel sheet containing 3.0-6.0 wt.% manganese, which is both coatable with liquid zinc and resistant to LME. The object of the present invention is also to make available an easy to implement method for obtaining said steel sheet, and an assembly which does not have LME problems after spot welding. [Means for solving the problem]
[0010] This object is achieved by providing a galvanized steel sheet as claimed in claim 1. Another object is achieved by providing an annealing treatment method as claimed in claim 2. The final object is achieved by providing a spot welded joint as claimed in claim 3. The spot welded joint may also have the features of claims 5-6.
[0011] Other features and advantages of the present invention will become apparent from the following detailed description of the invention.
[0012] The designation "steel" or "steel sheet" refers to steel sheets, coils, plates, the composition of which allows the parts to achieve tensile strengths of up to 2500 MPa, more preferably up to 2000 MPa, for example tensile strengths of 980 MPa or more, preferably 1270 MPa or more, or even 1470 MPa or more.
[0013] To illustrate the invention, various embodiments and implementations of non-limiting examples are described with particular reference to the following figures. [Brief description of the drawings]
[0014] [Figure 1] 1 shows an annealing thermal cycle according to the present invention with steps within the furnace. [Diagram 2] The layer at the interface between the base material and the zinc plating layer is shown. [Diagram 3]1 shows the carbon content at a depth of 20 μm measured from the interface with the plating layer as a function of dew point during the second heating step and the soaking step, the dark zone being according to the invention. [Figure 4] Shown is a spot welded assembly used to verify the LME resistance of steel plates. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] The present invention relates to a galvanized steel sheet, comprising, in weight percent, 0.08≦C≦0.3% 3.0≦Mn≦6.0% 0.5≦Si≦2.5% 0.003≦Al≦2.0% 0.01≦Mo≦0.5% 0.01≦Ti≦0.1% 0.01≦Nb≦0.08% 0.0002≦B≦0.005 Cr≦1.0% S≦0.010% P≦0.025% N≦0.008% The present invention relates to a galvanized steel sheet comprising:
[0016] Preferably, the weight percentage of manganese is greater than 3.5%.
[0017] Preferably, the weight percentage of silicon is greater than 0.7%, advantageously greater than 10%.
[0018] In addition, the present invention is characterized in that, as measured from the interface between the base material (20) and the zinc plating layer (22) in FIG. a) a decarburized layer (21) starting from the interface with the coating layer and having a carbon content of less than 0.1 weight percent at a depth of 20 μm; b) the decarburized layer includes a ferrite sublayer (211) starting from the interface with the plating layer, the ferrite content being greater than 70% in cross-sectional area at a depth of at least 3 μm; c) the ferrite sublayer includes an internal oxide selective zone (212) beginning at the interface with the plating layer, having a depth of at least 2.5 μm, and containing manganese oxide, silicon oxide, and optionally aluminum oxide; This relates to galvanized steel sheets.
[0019] The inventors have found that a steel sheet has better resistance to LME by reducing the carbon content in the interface layer in contact with the galvanized layer. Indeed, carbon appears to be a highly sensitive element to LME. Without being bound by theory, the inventors have found that to provide good LME resistance, the carbon content at a depth of 20 μm from the interface with the galvanized layer must be less than 0.1 weight percent. Preferably, the carbon content at a depth of 20 μm from the interface with the galvanized layer is less than 0.08 weight percent or even less than 0.06 weight percent.
[0020] The inventors have also found that ferritic microstructures have better LME resistance than layers composed of other phases. The small amount of carbon in ferrite compared to other phases appears to be beneficial for LME resistance. Layers with a ferrite content of more than 70% by cross-sectional area are required to have a depth of at least 3 μm, preferably 4 μm or even 5 μm.
[0021] The inventors have found that the selective internal oxidation zone has a beneficial effect on liquid metal embrittlement (LME) resistance. Without being bound by theory, it is believed that elements contained in the internal oxidation zone, such as silicon, manganese and aluminum, are present in lesser amounts in solid solution at the direct interface with the galvanized layer. Indeed, silicon appears to be the element sensitive to LME. The inventors have found that in order to provide good LME resistance, the internal selective oxidation zone must be at least 2.5 μm. Preferably, the internal oxidation selective zone starting from the interface with the galvanized layer has a depth of at least 3.5 μm or even 4.5 μm.
[0022] The present invention relates to a method for producing the galvanized steel sheet, comprising the following steps (see FIG. 1): i. A preheating process in a direct fired furnace (DFF) section 11, where the oxidizer / fuel ratio is 1.00 or greater; ii. heating in a radiant tube heating (RTH) section 12 under a reducing atmosphere containing at least 1% by volume hydrogen with the balance being nitrogen to a soaking temperature of at least Ae3-10°C, with a dew point of at least 0°C, where Ae3 is determined by dilatometry; iii. soaking in a radiant tube soaking (RTS) section 13 at a soaking temperature with a dew point of at least 0° C. under a reducing atmosphere containing at least 1% by volume of hydrogen and the balance being nitrogen; iv. A cooling step 14 under a reducing atmosphere containing at least 1% by volume of hydrogen, the remainder being nitrogen, with a dew point below -20°C. v. Overaging or carbon enrichment process15 vi. Zinc plating process 16 The present invention relates to a method comprising the steps of:
[0023] Such an annealing treatment according to the invention allows for good coatability and good LME resistance, as shown in FIG.
[0024] During the preheating step in DFF, it is essential to control the oxidation of the surface by the lambda value (λ), which is usually defined as the ratio of the amount of oxidizer to fuel in the furnace atmosphere. To ensure good coating ability, lambda must be at least 1.00, preferably at least 1.02 or 1.04.
[0025] The steps following heating in the DFF are important for surface decarburization and internal selective oxidation, both of which are related to the subsequent LME resistance of the steel sheet. The atmosphere must be controlled. The dew point in the radiant tube furnace is very important, as shown in FIG. 3. Without being bound by any theory, it is believed that a dew point above 0° C. is necessary in both the RTH of step ii and the RTS of step iii to achieve the desired layers, sublayers and zones a), b) and c) at the interface between the base metal and the coating layer. Preferably, the atmosphere in the RTH and RTS has a dew point of at least 3° C., advantageously at least 5° C. or even 7° C.
[0026] In contrast to prior art processes such as that disclosed in EP 3396005, the annealing cycle of the present invention includes a soaking step at 800°C or higher to ensure full recrystallization of the steel sheet. Preferably, the soaking step in step iii. may be carried out at a temperature of at least 820°C or 840°C.
[0027] In the steps following the soaking in the RTS, a very dry atmosphere is required to avoid re-oxidation of the surface, which would in fact reduce the coatability of the steel sheet in the liquid zinc. The dew point of the atmosphere in these steps must be below -20°C. Preferably, the atmosphere during the cooling and final steps has a dew point below -25°C, advantageously below -40°C.
[0028] After annealing and galvanizing, the steel sheets are cut into blanks. The blanks are then deformed, for example by press stamping, to obtain parts. The parts are assembled to other steel parts by welding, for example by resistance spot welding. Cracks in spot welded joints are detrimental to their resistance.
[0029] The present invention also relates to a spot welded joint containing an average of less than 0.5 cracks having a length of more than 100 μm due to the spot weld, the longest crack having a length of less than 300 μm.
[0030] Preferably, the spot weld joint contains on average less than 0.5 cracks due to the spot welds having a length greater than 80 μm, or less than 0.5 cracks due to the spot welds having a length greater than 60 μm.
[0031] Preferably, the longest crack is less than 200 μm, or less than 100 μm.
[0032] The invention is described below in trials carried out for informational purposes only and not for limitation. EXAMPLES
[0033] In this example, a Mn-containing steel was used having the following composition, expressed in weight percent in Table 1:
[0034] [Table 1]
[0035] Cold rolled steel coils having such composition were subjected to continuous annealing and galvanizing lines.
[0036] The annealing furnace had several sections. The first heating section, called DFF11, is heated by direct fire. The second heating section is by a radiant tube called RTH12, The heat equalization section is equipped with a radiant tube called RTS13. a first cooling section called annealing 14; A second cooling section called quenching, Carbon enrichment section 15, Galvanized Section 16.
[0037] The process parameters during annealing are shown in Table 2.
[0038] [Table 2]
[0039] The coils were then cut into samples for further analysis. The samples are still designated by their original run numbers, with each run number corresponding to specific process parameters highlighted in Table 2.
[0040] A set of samples cut for analysis was examined to obtain the internal oxidation depth and the depth of the decarburized layer.
[0041] The depth of internal oxidation of galvanized steel sheets was measured on images observed with a scanning electron microscope (SEM) near the steel sheet surface. Internal oxides appear near the interface with the coating layer at the grain boundaries and internal grains of the base steel sheet. The depth of internal oxidation was defined by measuring the minimum depth from the interface between the coating layer and the deepest point where the oxide was observed. Observations were made in the plan RD-ND (rolling direction-normal direction) at a magnification of more than 5000x.
[0042] The thickness of the sublayer containing at least 70% ferrite by volume fraction was determined in the same manner as the depth of the internal oxidation.
[0043] The volume fraction of ferrite is determined as the average value of the ferrite area fractions measured on the images in the RD-ND (rolling direction-normal) plane. Glow discharge optical emission spectroscopy (GDOES) qualitative and quantitative analysis was performed on the carbon content at a depth of 20 μm in the steel sheet measured from the interface with the coating layer. Three GDOES analyses on both sides of the sample, starting from the potentiometric dissolution of the coating coating layer before the GDOES measurement. All depths are then expressed in iron equivalents (μm(e,q,Fe)). The results are summarized in Table 3.
[0044] [Table 3]
[0045] Trials 1 and 2 according to the invention for the internal oxidation zone, ferrite sublayer and decarburized layer underwent an atmosphere with a positive dew point in both the RTH and RTS sections.
[0046] Trials 3 and 4, which are not in accordance with the invention with respect to the internal oxidation zone, ferrite sublayer and decarburized layer, were subjected to an atmosphere having at least one negative dew point in RTH or RTS.
[0047] Another set of samples was subjected to LME resistance testing with spot welding.
[0048] The LME crack resistance behavior was evaluated using a three-ply stacking condition as shown in Figure 4. For each trial, three coated steel plates were welded by resistance spot welding. The plate to be tested (41) was at the top and two mild steel plates (42) and (43) were at the bottom. The spot weld assembly was performed with an electrode of 8 mm radius with a clamping force of 500 daN. The welding cycle consisted of three pulses of 0.2 s duration each with a cooling time of 0.04 s between each pulse.
[0049] After welding, all welds are carefully inspected, first using dye penetrant testing (DPI) and then using metallographic analysis. DPI is performed after chemically removing the galvanized Zn layer, which helps in locating the outer cracks. Metallographic analysis is performed at the central cross section of the weld based on the DPI observation. The metallographic specimens are placed in epoxy resin, mechanically polished to 1 micron polishing cloth, and then etched in picric acid solution. The distribution of cracks is then observed and classified under an optical microscope, the length of all visible LME cracks is measured, and their number per crack category is recorded.
[0050] Next, the number of cracks having a length of 100 μm or more and the maximum crack length were evaluated using an optical microscope.
[0051] The results are shown in Table 4.
[0052] [Table 4]
[0053] Trials 1 and 2 according to the invention show superior resistance to LME compared to trials 3 and 4. Indeed, for trials 1 and 2, there are no cracks longer than 100 μm.
Claims
1. A galvanized steel sheet having the following composition, in weight percent: 0.08≦C≦0.3% 3.0≦Mn≦6.0% 0.5≦Si≦2.5% 0.003≦Al≦2.0% 0.01≦Mo≦0.5% 0.01≦Ti≦0.1% 0.01≦Nb≦0.08% 0.0002≦B≦0.005 Cr≦1.0% S≦0.010% P≦0.025% N≦0.008% and made from a steel base material having a composition including inevitable impurities from the manufacturing process, the remainder being iron; The steel sheet has a thickness measured from the interface between the base material (20) and the zinc plating layer (22), a) a decarburized layer (21) starting from the interface with the plating layer and having a carbon content of less than 0.1 weight percent at a depth of 20 μm; b) the decarburized layer includes a ferrite sublayer (211) starting from the interface with the plating layer and having a depth of 3 μm or more, and the ferrite content is more than 70% in terms of cross-sectional area ratio; c) the ferrite sublayer includes an internal oxide selective zone (212) beginning at the interface with the plating layer, having a depth of at least 2.5 μm, and containing manganese oxide, silicon oxide, and optionally aluminum oxide. Galvanized steel sheet.
2. 1. A method for producing galvanized steel, comprising the steps of: 0.08≦C≦0.3% 3.0≦Mn≦6.0% 0.5≦Si≦2.5% 0.003≦Al≦2.0% 0.01≦Mo≦0.5% 0.01≦Ti≦0.1% 0.01≦Nb≦0.08% 0.0002≦B≦0.005 Cr≦1.0% S≦0.010% P≦0.025% N≦0.008% and made from a steel base material having a composition including inevitable impurities from the manufacturing process, the remainder being iron; The method comprises the following steps of an annealing heat treatment cycle prior to galvanizing: i. a preheating step in a direct fired furnace (DFF) section (11) having an oxidant / fuel ratio of 1.00 or greater; ii. heating in a radiant tube heating (RTH) section (12) under a reducing atmosphere containing at least 1% by volume of hydrogen and the balance being nitrogen, with a dew point of at least 0° C., to a soaking temperature of at least Ae3-10° C., where Ae3 is determined by dilatometry; iii. a soaking step in a radiant tube soaking (RTS) section (13) at a soaking temperature having a dew point of at least 0° C. under a reducing atmosphere containing at least 1% by volume of hydrogen and the balance being nitrogen; iv. Cooling (14) under a reducing atmosphere containing at least 1% by volume of hydrogen, the remainder being nitrogen, with a dew point below −20° C. v. Overaging or carbon enrichment step (15) vi. Zinc plating process (16) The method includes:
3. A spot welded joint of at least two metal plates including at least the steel plate according to claim 1, the joint containing an average of less than 0.5 cracks having a length of more than 100 μm due to the spot welding, and the longest crack having a length of less than 300 μm.
4. The spot welded joint according to claim 3 , wherein the second metal plate is a steel plate or an aluminum plate.
5. 5. The spot welded joint according to claim 4, wherein the second metal sheet is a steel sheet according to claim 1 or a steel sheet obtainable from the method according to claim 2.
6. The spot welded joint according to any one of claims 3 to 5, further comprising a third metal plate which is a steel plate or an aluminum plate.
Citation Information
Patent Citations
Method of manufacturing alloyed hot-dip galvanized steel sheet
JP2016017193A
High-strength hot-dip galvanized steel sheet with excellent surface quality and spot weldability, and its manufacturing method
JP2019504196A
Method for producing galvannealed steel sheet resistant to liquid metal embrittlement - Patent Application 20070122997
JP2020521041A
Steel plate with excellent toughness, ductility and strength and manufacturing method thereof
JP2021508769A
Steel annealing method
JP2023525519A
